THE INSPIRATION BUILDING PROCESS IN BUDDHISM - Pawasut, Amporn (Journal of Buddhist Anthropology, 2020)
This research paper is documentary research aims are to analyze, synthesize the inspiration building process in Buddhism, to studying concepts and theories about inspiration and to studying the inspiration in the event of it appears in Buddhist scriptures. The results have shown the inspiration building process in Buddhism since in The Buddha’s time, based on the three main qualities of inspiration: evocation, approach motivation, and transcendence. That is 1) The characterizes of evocation of illumination or the insight with unwilled. That is the Buddha who has intrinsic inspiration building by nurture, education and social environment which belief in the afterlife and persons try to find the way out of Samsara then entered monkhood and practice perseverance. Then he recalls the situation by mindful of the experience he entered and remained in the first absorption: thought conception, discursive thinking, rapture, and pleasure born of seclusion while he sat under the rose-apple tree. The idea imbues “that is the path to enlightenment”. 2) That illumination approach motivates the goal for enlightened. 3) These are the process of self-transcendence to be free beyond self, abandon of reborn by using the way of Yonisomanasikara and perseverance. After the enlightenment found the inspiration building process by Dhamma talk to expand from within-person to between-persons, obviously shares personal knowledge and experiences to others by generosity and kindness.